Systematic review with meta-analysis: Efficacy and safety of biological treatment on salivary gland function in primary Sjögren’s syndrome - Wang, Xiaoyan; Lin, Xiang; Su, Yingying; Wang, Hao (Frontiers in Pharmacology, 2023)
Objective To assess the efficacy and safety of clinical trials of biologics in improving the salivary gland (SG) function in primary Sjögren’s syndrome (pSS), which has not been analyzed critically and systematically. Methods Pubmed, Web of Science, ClinicalTrials.gov, EU Clinical Trials Register and Cochrane Library were searched for clinical trials that reported effects of biological treatment on the SG function and safety in pSS patients. Inclusion criteria were defined following PICOS (participants, interventions, comparisons, outcome and study design) recommendations. The objective index (the change of unstimulated whole saliva flow, UWS), and the serious adverse event (SAE) were assessed as main outcome measures. A meta-analysis of the efficacy and safety of the treatment was conducted. Quality assessment, sensitivity analysis and publication bias were assessed. The effect size together with 95% confidence interval was used to estimate the efficacy and safety of biological treatment, and was plotted as a forest plot. Results The literature search yielded 6678 studies, 9 of which fulfilled the inclusion criteria, with 7 randomized controlled trials (RCT), and 2 non-RCT clinical studies. Generally, biologics did not significantly increase the UWS from baseline of pSS patients than the control group at matched time point (p = 0.55, standardized mean difference, SMD = 0.05, 95% confidence interval, CI: -0.11, 0.21). However, pSS patients with shorter disease duration (≤3 years, SMD = 0.46, 95% CI: 0.06, 0.85) were prone to have a better response to biological treatment by showing higher increased UWS than patients with longer disease duration (> 3 years, SMD = -0.03, 95% CI: -0.21, 0.15) (p=0.03). For the meta-analysis of the safety of biological treatment, the SAEs in the biologics group were significantly higher than the control group (p=0.0021, log odds-ratio, OR = 1.03, 95% CI: 0.37, 1.69). Conclusion Biological intervention during the early course of the disease may benefit pSS patients better than during the late course. Significantly more SAEs in the biologics group indicate that the safety of biologics needs to be addressed for future biological clinical trials and treatment.